2014
DOI: 10.1088/0031-9155/59/17/4913
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pregnancy stage and fetus position on the whole-body and local exposure of the fetus to RF-EMF

Abstract: This paper analyzes the influence of pregnancy stage and fetus position on the whole-body and brain exposure of the fetus to radiofrequency electromagnetic fields. Our analysis is performed using semi-homogeneous pregnant woman models between 8 and 32 weeks of amenorrhea. By analyzing the influence of the pregnancy stage on the environmental whole-body and local exposure of a fetus in vertical position, head down or head up, in the 2100 MHz frequency band, we concluded that both whole-body and average brain ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In [ 24 ], the variability of the exposure due to the fetal posture was quantified on three pregnant woman models at three months GA, in which the fetal posture was changed among the most statistically significant at that stage of pregnancy. A detailed description of the various fetal positions during pregnancy is provided in [ 45 ]. The three months GA pregnant models were exposed to uniform B -field oriented with respect to the classical directions B front , B lat and B top .…”
Section: Resultsmentioning
confidence: 99%
“…In [ 24 ], the variability of the exposure due to the fetal posture was quantified on three pregnant woman models at three months GA, in which the fetal posture was changed among the most statistically significant at that stage of pregnancy. A detailed description of the various fetal positions during pregnancy is provided in [ 45 ]. The three months GA pregnant models were exposed to uniform B -field oriented with respect to the classical directions B front , B lat and B top .…”
Section: Resultsmentioning
confidence: 99%
“…To add to the complexity of the issue, the estimation of fetus RF exposure induced by wireless communication systems is highly complex because the exposure depends on many parameters (source, usage, frequency, posture, age of fetus). Specific absorption models showed that the fetus is exposed to various RF-EMF from the mother holding her cell phone close to her head or her body, depending on the position of the fetus and the pregnancy week [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, specific absorption rate (SAR) models indicate that RF-EMF from the mother holding the cell phone to her head or near the body would only result in very low SAR levels to reach the fetus (below the basic restriction of 0.08 W kg −1 )(Varsier et al, 2014); and these SAR models vary depending on pregnancy stage and position of the fetus, relying on many assumptions and extrapolations (Dimbylow, 2007; Dimbylow et al, 2009; Varsier et al, 2014). Also, RF-EMF exposure to the fetus could depend on where the mother carries her cell phone (Sudan et al, 2016), data which was not available for this analysis.…”
Section: Discussionmentioning
confidence: 99%